The relationship between caries in the primary dentition at 5 years of age and permanent dentition at 10 years of age – a longitudinal study - M. S. SKEIE, M. RAADAL, G. V. STRAND, & I. ESPELID (Paediatric Dentistry, 2006)
To explore a possible relationship between the caries experience and pattern in the primary dentition at 5 years of age and the permanent dentition at 10 years of age.